MODEL PEMBELAJARAN FIQIH BERBASIS KITAB KUNING DI MADRASAH TSANAWIYAH DARUN NAJAH KARANGPLOSO - Karima Indah Riyati; Fathurrahman Alfa; Indhra Musthofa (VICRATINA, 2020)
In this study, researcher focuses on lesson planning, lesson implementation, also the characteristics in Fiqih based on Kitab Kuning at Madrasah Tsanawiyah Darun Najah Karangploso. To achieve thit study, researcher uses qualitative method with data collection using observation, interview, and documentation during research process. To achieve this study researchers used a type of field study. The result of this study is the head master decided to use yellow book in lesson planning since the very beginning of Madrasah. This is done to make the generation of tafaqquh fi al-ddin. In the implementation process, teachers should adjust the curriculum from the government with the study exist in Kitab Salafin accordance with the material needed by the students. According to the researcher, the using of Kitab Kuning as the learning media is one of unique characteristicsin this Madrasah.  Key words : Salafi School, Yellow Book, Learning